REGULARITIES OF СOMPENSATORY-ADAPTIVE REACTIONS IMMUNE RESPONSE OF WORKERS IN CHRONIC EXPOSURE TO VINYL CHLORIDE - G. M. Bodienkova; R. Yu. Alexeyev (Acta Biomedica Scientifica, 2012)
Laboratory and immunological study of male workers in the production of vinyl chloride was conducted. It has established that more pronounced stress of compensatory-adaptive reactions is observed in patients with incipient neurointoxication ("at risk”) in comparison to group of ‘healthy”. With increasing radiation exposure to vinyl chloride, duration (length of) exposure, as well as increasing the concentration of chloride in the blood, showed worsening of changes in the immune system of workers. Installed elevated levels of autoantibodies: the S-100, B-head. Ca-channel and the DNA appear to be indicative of early changes in certain structures of the nervous system. Some of the earliest and most sensitive indicators of the formation of body resistance to unfavorable working environment are: IgM, IL-1β, TNF-α, IL-8, autoantibodies to S-100, autoantibodies to the В-head. Ca-channel, autoantibodies to DNA.